Experimental study of the mechanical properties of simple and fiber-reinforced concrete under monotonic loading - Reyna Salazar, Roy (2022)
Concrete is one of the main building materials in Peru and worldwide, the study of its mechanical properties and concrete mix elaboration have been extensively developed over time. In the last years, new ways of elaboration with different materials have been searched, in order to improve its mechanical properties, including the fiber reinforced concrete. The study of its strain-stress mechanical properties of fiber reinforced concrete under monotonic load is the objective of this investigation, based on experimental tests performed in 90 samples, taking into account the influence of many factors, such as: Compression strength design, sample section geometry (square or circular section), slenderness (height/depth ratio), and the comparison of the reinforced concrete with its equivalent plain concrete in terms of mix design. From the experimental results, the use of fiber reinforcement increases the deformation capacity of the concrete under monotonic compression, but its resistance is not improved significantly. On the other hand, square section specimens have a higher deformation capacity for slenderness 1:2 and 1:3 in comparison with circular section specimens.